2021
DOI: 10.1088/1741-4326/abe804
|View full text |Cite
|
Sign up to set email alerts
|

Pedestal stability analysis on MAST in preparation for MAST-U

Abstract: In preparation for the upcoming MAST-U campaign, pedestal stability of spherical tokamaks is revisited by investigating standard H-mode discharges on MAST. As a step beyond previous studies, both ion and electron profiles are used for obtaining equilibria and a diverse set of pedestals is evaluated. Stability analysis with the ELITE and CGYRO codes shows that MAST pedestals are constrained by kinetic ballooning modes and medium toroidal mode number peeling-ballooning modes, with most unstable modes ranging fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…The shots also have long periods of type I ELMs with a high amount (for MAST) of ELM cycles, such that ELM averaged profiles can be used. In both configurations the experimental point is located in the unstable region close to the ballooning boundary, consistent with [21]. Note that not all MAST type I ELMs are in this unstable region.…”
Section: Mast Elm Data For Europed Inputssupporting
confidence: 83%
See 2 more Smart Citations
“…The shots also have long periods of type I ELMs with a high amount (for MAST) of ELM cycles, such that ELM averaged profiles can be used. In both configurations the experimental point is located in the unstable region close to the ballooning boundary, consistent with [21]. Note that not all MAST type I ELMs are in this unstable region.…”
Section: Mast Elm Data For Europed Inputssupporting
confidence: 83%
“…In most MAST type I regimes, that are not mixed with type II ELMs, the experimental point is positioned on or close to the ballooning boundary [21]. As shown in section 4, the type I pedestal experimental point is usually at a lower current density than the P-B nose and is usually ballooning unstable.…”
Section: Analysis Of Type II Experimental Datamentioning
confidence: 98%
See 1 more Smart Citation
“…The ion temperature is assumed equaled to electron temperature in this simulation. Note that the influence of ion vs electron temperature in the pedestal for linear stability is not significant, which has been shown by the reference [27] with ELITE.…”
Section: Equilibria For the East High-β P Long-pulse Experiments And ...mentioning
confidence: 66%
“…However, it was found that in spherical tokamaks (STs) this model can be less reliable. While in past studies ELMing discharges in MAST have been found to be limited by ideal ballooning modes [9,10], this is not the case for NSTX. Here, ideal PB mode stability thresholds can be strongly underestimated, such that ELMing plasmas are predicted to sit deep inside the stable domain [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 85%